Petaloid-shaped ZnO coated carbon felt as a controllable host to construct hierarchical Li composite anode. (May 2020) - Yue, Xin-Yang; Bao, Jian; Yang, Si-Yu; Luo, Rui-Jie; Wang, Qin-Chao; Wu, Xiao-Jing; Shadike, Zulipiya; Yang, Xiao-Qing; Zhou, Yong-Ning
Abstract: Prestoring Li metal into the 3D host via thermal infusion strategy has been considered as an effective approach on suppressing Li dendrites growth of Li-metal anode during cycling. However, the fast Li infusing process generally induces uncontrollable and undesirable structures during the formation of composite Li metal anode. It is widely accepted that both physical and chemical interactions between the molten Li and the hosts provide driving forces for Li infusing into the host, but which one plays the dominant role has not been explored clearly. In this work, a 3D carbon felt coated by petaloid zinc oxide (CFZO) is designed as a controllable host for prestoring Li metal via thermal infusion method. It is revealed that the morphology induced physical driving force plays a more important role than the chemical reaction between ZnO and molten Li in the thermal infusion process. The physical driving force originates from the capillarity effect, depending on the roughness of the host according to Wenzel's model. An adjustable Li infusing process can be controlled to fabricate the Li composite electrode with a hierarchical structure (with dense Li-rich layer and porous Li-poor layer). The unique structure of the CFZO-Li not only provides enough spaces for Li deposition, but also disperses local current density to induce a uniform Li deposition behavior, thus Li dendrites can be suppressed effectively. As a result, CFZO-Li anode exhibits promising cycle stability when coupled with both Li-containing (LiNi0.8 Co0.15 Al0.05 O2 ) and Li-free (sulfur) cathodes. Graphical abstract: A petaloid-shaped ZnO coated carbon felt host results in a hierarchical Li electrode after controlling the Li infusing process. The chemical driving forces slightly affect the Li wettability of CF host, while the capillary effect as a physical driving force resulted from the micro-morphology of ZnO coating plays a dominant role in controlling Li infusion process. Image 1 Highlights: CFZO is designed as a controllable host for pre-storing Li metal via thermal infusion method. A unique hierarchical-structural Li electrode with dense Li-rich layer and porous Li-poor layer is obtained. Physical driving force (capillary effect) plays a dominant role in the Li infusing process. Surface roughness of the host is the key factor that impacts the capillary effect based on Wenzel's model. CFZO-Li anode can suppress dendrite growth effectively and exhibits promising electrochemical performance.